Outcomes of Norovirus diarrheal infections and Clostridioides difficile infections in kidney transplant recipients: A single‐center retrospective study. Issue 2 (11th February 2019) - Rolak, Stacey; Di Bartolomeo, Sarah; Jorgenson, Margaret R.; Saddler, Christopher M.; Singh, Tripti; Astor, Brad C.; Parajuli, Sandesh
Abstract: Recently, Norovirus has been recognized as an important cause of diarrheal infection in kidney transplant recipients (KTRs). We assessed the risk factors and outcomes of Norovirus diarrheal infections (NVDI) and Clostridioides difficile infection (CDI) on graft and patient survival following kidney transplant (KT). We examined KTRs transplanted at our center between 1994 and 2014, and compared those who suffered from NVDI and CDI with patients who did not develop either infection. Each patient with NVDI or CDI was matched with five controls based on time from transplant. Of the 4941 KTs performed during the study period, there were 2112 evaluable cases: 66 NVDI cases, 286 CDI cases, and 1760 controls. Median uncensored graft survival following infection was 497.5 days for the NVDI group, 440 days for the CDI group, and 1271 days for controls. Those with CDI had significantly inferior graft survival than controls (HR 2.41; CI 2.01, 2.90; P  < 0.001), and those with NVDI had a 23% lower risk of graft survival than controls (HR 1.23; CI 1.0, 1.52; P  = 0.054). Diarrheal infection after KT is associated with reduced long‐term graft survival.